ChemInform Abstract: Cyclobutane and Cyclobutene Synthesis: Catalytic Enantioselective [2 + 2] Cycloadditions. Issue 47 (November 2015) - Xu, Yao; Conner, Michael L.; Brown, M. Kevin
Abstract: Review: [55 refs.